Transient Triplet Differential (TTD) Method for Background Free Photoacoustic Imaging - Joel W. Y. Tan (Nature Portfolio, 2018)
Abstract With the capability of presenting endogenous tissue contrast or exogenous contrast agents in deep biological samples at high spatial resolution, photoacoustic (PA) imaging has shown significant potential for many preclinical and clinical applications. However, due to strong background signals from various intrinsic chromophores in biological tissue, such as hemoglobin, achieving highly sensitive PA imaging of targeting probes labeled by contrast agents has remained a challenge. In this study, we introduce a novel technique called transient triplet differential (TTD) imaging which allows for substantial reduction of tissue background signals. TTD imaging detects directly the triplet state absorption, which is a special characteristic of phosphorescence capable dyes not normally present among intrinsic chromophores of biological tissue. Thus, these triplet state absorption PA images can facilitate “true” background free molecular imaging. We prepared a known phosphorescent dye probe, methylene blue conjugated polyacrylamide nanoparticles, with peak absorption at 660 nm and peak lowest triplet state absorption at 840 nm. We find, through studies on phantoms and on an in vivo tumor model, that TTD imaging can generate a superior contrast-to-noise ratio, compared to other image enhancement techniques, through the removal of noise generated by strongly absorbing intrinsic chromophores, regardless of their identity.